The Cell Biology of the Trichosporon-Host Interaction - Duarte-Oliveira, Cláudio; Rodrigues, Fernando; Gonçalves, Samuel M.; Goldman, Gustavo H.; Carvalho, Agostinho; Cunha, Cristina (Frontiers in Cellular and Infection Microbiology, 2017)
Fungi of the genus Trichosporon are increasingly recognized as causative agents of superficial and invasive fungal disease in humans. Although most species are considered commensals of the human skin and gastrointestinal tract, these basidiomycetes are an increasing cause of fungal disease among immunocompromised hosts, such as hematological patients and solid organ transplant recipients. The initiation of commensal or pathogenic programs by Trichosporon spp. involves the adaption to the host microenvironment and its immune system. However, the exact virulence factors activated upon the transition to a pathogenic lifestyle, including the intricate biology of the cell wall, and how these interact with and subvert the host immune responses remain largely unknown. Here, we revisit our current understanding of the virulence attributes of Trichosporon spp., particularly T. asahii, and their interaction with the host immune system, and accommodate this knowledge within novel perspectives on fungal diagnostics and therapeutics.